Trehalulose: Exploring its benefits, biosynthesis, and enhanced production techniques - Seevanathan, Yogaletchumy; Zawawi, Norhasnida; Salleh, Abu Bakar; Oslan, Siti Nurbaya; Ashaari, Nur Suhanawati; Amir Hamzah, Amir Syahir; Sabri, Suriana (Elsevier, 2024)
The increasing concern over sugar-related health issues has sparked research interest in seeking alternatives to sucrose. Trehalulose, a beneficial structural isomer of sucrose, is a non-cariogenic sugar with a low glycemic and insulinemic index. Besides its potential as a sugar substitute, trehalulose exhibits high antioxidant properties, making it attractive for various industrial applications. Despite its numerous advantages and potential application in various sectors, the industrial adoption of trehalulose has yet to be established due to lack of studies on its characteristics and practical uses. This review aims to provide a comprehensive overview of the properties of trehalulose, emphasizing its health benefits. The industrial prospects of trehalulose as sweetener and reducing agent, particularly in food and beverages pharmaceutical, and cosmeceutical sectors, are explored. Additionally, the review delves into the sources of trehalulose and the diverse organisms capable of producing trehalulose. The biosynthesis of this sugar primarily involves an enzyme-mediated process. Thus, these enzymes' properties, mechanisms, and the heterologous expression of genes associated with trehalulose production are explored. The strategies discussed in this review can be improved and applied to establish trehalulose bio-factories for efficient synthesis of trehalulose in the future. With further research and development, trehalulose holds promise as a valuable component across various industries.